2012
DOI: 10.1038/onc.2012.588
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia attenuate hedgehog signalling in neoplastic chondrocytes

Abstract: Primary cilia can act as either a negative or positive regulator of the hedgehog (Hh) signaling pathway. Many cartilage tumors are characterized by abnormal activation of the Hh pathway. Here, we report that the presence of primary cilia occurs at a low frequency (12.4%) in neoplastic chondrocytes from malignant human chondrosarcomas, compared with chondrocytes from normal articular cartilage (67.7%). To determine the function of primary cilia in cartilaginous neoplasia, we studied benign cartilage tumors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
5
51
1
Order By: Relevance
“…In tumors such as chondrosarcoma, which rely on ligand-dependent Hh activation and exhibit high levels of GLI1 and PTCH1 expression, downregulation of GLI1 and PTCH1 could serve as biomarkers for response to Hh pathway inhibition. In addition, as most chondrosarcomas have an identifiable primary cilium, the presence of cilia may serve as a biomarker for response to Hh blockade, as recently demonstrated in a transgenic mouse model of cartilage neoplasia (46). As a potential treatment for patients, IPI-926, a potent and selective SMO antagonist, may have advantages as targeted therapy for Hh-dependent tumors compared with other pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors such as chondrosarcoma, which rely on ligand-dependent Hh activation and exhibit high levels of GLI1 and PTCH1 expression, downregulation of GLI1 and PTCH1 could serve as biomarkers for response to Hh pathway inhibition. In addition, as most chondrosarcomas have an identifiable primary cilium, the presence of cilia may serve as a biomarker for response to Hh blockade, as recently demonstrated in a transgenic mouse model of cartilage neoplasia (46). As a potential treatment for patients, IPI-926, a potent and selective SMO antagonist, may have advantages as targeted therapy for Hh-dependent tumors compared with other pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In human chondrosarcomas, the percentage of ciliated neoplastic chondrocytes is only 12.4%, which is a very low frequency as compared with 67.7% in normal articular cartilage (Ho et al 2013). In the mouse peripheral chondrosarcoma, primary cilia are absent on the majority of chondrocytes, which might contribute to the loss of polarity of chondrocytes in peripheral chondrosarcoma (de Andrea et al 2015).…”
Section: Primary Cilia/ift In Bone Tumorsmentioning
confidence: 99%
“…Similar to Col2α1-Gli2 mice, IFT88 +/-mice (partial loss IFT88 leads a partial loss of ciliogenesis) also develop cartilage tumors. More evidence demonstrates that the disruption of cilia (by decreasing IFT88 expression or treating with choral hydrate) in Gli2-overexpressed chondrosarcomas results in further activation of the Hh signaling pathway and promotes tumor growth, suggesting that cilia act as an inhibitor of Hh signaling in neoplastic chondrocytes (Ho et al 2013). A recent study suggested that loss of primary cilia in chondrocytes creates a proliferative block and might help to select those cells that have lost cell-cycle regulatory genes, which promotes tumor growth (de Andrea et al 2015).…”
Section: Primary Cilia/ift In Bone Tumorsmentioning
confidence: 99%
See 2 more Smart Citations